Censorship of Pacifist Movements through Religious Arguments - Bill Bolin (Revue LISA)
The number of wars in which English-speaking countries, primarily the United States and Great Britain, have been involved in the past one hundred years might leave the impression that peace movements are ineffectual. Virtually every war in recent US and UK history has had its corresponding anti-war protests, and there is no record of a peace movement actively stopping an impending military action at inception, although evidence exists that peace movements have affected martial policy after the initial stages of a military action. Instead, peace movements seem to elicit ill will and accusations of self-preservation and treason. This article argues that peace movements are thus censored through a sense of patriotism constructed by those in positions of influence, including government entities and the press. Primary focus is on the United States and Europe in advance of both the Great War and the global War on Terror because those two serve as bookends for the twentieth century, and they both provide examples of global conflicts.